The Theoretical Discussions of Aesthetic in Pakistani Urdu - Naeem Mazhar; Muhammad Idrees Cheema (بازیافت, 2022)
The consciousness of beauty and beauty existed from the time of the creation of the universe. Humans along with the evolution of consciousness, there was diversity in the concept of beauty. At the beginning of history, human nature was the greatest guide for man. To whom various things and tools were made by seeing. This is the beginning of the arts and humanities. It led to the evolution of life. The beginning of civilization is the fruit of good thinking. As attention grew, the art began to evolve. This article explores the theoretical discussions of aesthetics among Pakistani Urdu scholars.